Multi-center evaluation of the first, low-cost, open source and totally 3D-printed pediatric laparoscopic trainer - Alexis Lubet; Mariette Renaux-Petel; Jean-Baptiste Marret; Julien Rod; Louis Sibert; Laurent Delbreilh; Agnès Liard (Heliyon)
Objective: This study created and evaluated the face validity of a novel, low-cost, three-dimensional printed pediatric laparoscopic trainer and compared it to a standard laparoscopic trainer (LT). Design: We developed the Space Child Laparoscopic Trainer (SCLT) using fused deposition modeling technology with a Bambulab P1S 3D printer.The cost per unit was five euros and the assembly time was 10 min. The printing time was 543 min for 434 g of polylactic acid filament (PLA). A smartphone was used as the camera.The performance of experienced surgeons and surgical residents was evaluated on SCLT and LT using the Objective Structured Assessment of Technical Skill score (OSATS) and time spent. Two fundamental laparoscopic tasks, peg transfer and precision cutting, were randomly performed by each trainer. Participant satisfaction was assessed using a questionnaire. This study assessed the learning speed of surgical residents using the SCLT compared to a standard LT through a non-inferiority test. The test results were compared with those of a control group of experienced senior surgeons. Setting: A medical training program was set up for first-year surgery residents from different French cities (Rouen, Caen, Amiens, and Lille) at the Medical Training Center of Rouen, in collaboration with the University Hospital of Rouen. Participants: Ten pediatric surgeons with at least ten years of experience in laparoscopic surgery, 51 first-year surgical residents, and six external evaluators with at least five years of laparoscopic experience. Results: In total, 200 exercises were performed by 50 residents. The estimated learning speed was +0.139 (95 % confidence interval [CI]: +0.053–+0.252, p = 0.01) for LT and +0.153 (95%CI: +0.035–+0.243, p = 0.004) for SCLT. The estimated learning speed ratio for the SCLT compared to that for the LT was 1.10 (95%CI: 0.35–3.46, p = 0.09 for non-inferiority to 0.50). Conclusions: The results demonstrated a similar performance between the SCLT and standard LT for resident training in pediatric surgery. The widespread dissemination of this tool to residents and surgeons, especially in developing countries, may allow easier access to laparoscopic training.